Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

Language barriers within the Winnipeg regional health authority. Evidence and implications - Bowen, Sarah (Winnipeg Regional Health Authority, 2004)

Comparaisons internationales : un aperçu de l'accès aux soins de santé pour les communautés de langue officielle en situation minoritaire au Canada, en Espagne, en Belgique et en Finlande - Bureau d'appui aux communautés de langue officielle (Santé Canada, 2007)

Évaluation de la validité des preuves présentées dans l’étude intitulée "Language Barriers in Health Care Settings: An Annotated Bibliography of the Research Literature" - Bureau d'appui aux communautés de langue officielle (Santé Canda, 2008)

Communicative sensitivity in the bilingual healthcare setting: A qualitative study of language awareness - Irvine, Fiona. E.; Roberts, Gwerfyl. W.; Jones, Peter; Spencer, Llinos. H.; Baker, Colin. R.; Williams, Cen (Journal of Advanced Nursing, 2006)
Aim. This paper reports on the second phase of a national study in Wales. The research aimed to assess the level of Welsh language awareness amongst healthcare professionals across Wales, and to identify the factors that enhance language choice within service delivery. Background. The literature suggests that language sensitive healthcare practice is central to ensuring high quality care. However, it is evident that language barriers continue to compromise the quality of care within nursing and other health services. One issue that has received little attention is the level of language awareness that healthcare professionals currently demonstrate. Furthermore the factors that influence language choice for bilingual/multilingual speakers are not well explored in the literature. Methods. The study involved semi-structured interviews with a range of healthcare professionals in acute and community settings across Wales. Using a systematic sampling matrix, a purposeful sample of 83 professionals was selected to participate. Twenty-seven of the respondents were nurses, health visitors and midwives. The interviews focussed on the factors that facilitate or impede language sensitive healthcare practice. All interviews were audiotaped and, using a framework analysis approach, conceptual codes were developed and defined and categories and sub-categories were constructed to create thematic charts. Findings. Three main themes were identified: care enhancement, which focussed on the process and outcome of offering language choice to bilingual patients; organizational issues, which reflected issues relating to the infrastructure of service provision; and training implications, which focused on Welsh language learning in health care. Conclusions. Complex dynamics of language use are in operation within bilingual healthcare settings and organizational as well as individual factors are important in facilitating appropriate language use. Many of the issues highlighted are not peculiar to the Welsh context, but apply to healthcare settings across the world, where other minority languages are in use.

Language as a barrier to care for Xhosa-speaking patients at a South African paediatric teaching hospital - Levin, M. E. (South African Medical Journal = Suid-Afrikaanse Tydskrif Vir Geneeskunde, 2006)
BACKGROUND: Disease is closely linked to the social context in which we live. Difficulty with communication, cultural incompatibility between patients and health care providers and socioeconomic obstacles are important barriers to quality care when doctors and patients come from different backgrounds and speak different languages. Red Cross War Memorial Children's Hospital (RCH) is a paediatric teaching hospital in Cape Town where staff members communicate mainly in English or Afrikaans, while many patients speak Xhosa as their first language. OBJECTIVES: The study aimed to identify barriers to optimal care for Xhosa-speaking parents of patients at RCH. The contribution of language difficulties was assessed as a possible barrier to health care for this group. DESIGN: A questionnaire was developed and administered to 53 Xhosa-speaking parents of children admitted to the short-stay ward at RCH. The questionnaire examined parents' perceptions of barriers to their children's care, using openended questions, closed-ended questions and selection from lists. RESULTS: Parents experienced significant structural and socioeconomic barriers to access of health care for their children. Language and cultural barriers were cited by more parents as a major barrier to health care than structural and socioeconomic barriers. Parents did not have access to same-language practitioners, as only 6% of medical interviews were conducted partly or wholly in the patient's home language. Of the 94% of interviews where no Xhosa was spoken by medical staff, 21% were conducted with the aid of an interpreter (formal or ad hoc) and in 79% no interpreter was used. Parents experienced difficulties with understanding the doctors (64%), making themselves understood (54%) and asking questions (38%). Sixty-nine per cent of parents were dissatisfied with communication between themselves and their doctors and 45% were concerned about negative effects of poor communication on them or their children. Parents tended to blame their own linguistic limitation rather than those of the doctors.
Keywords: Adolescent; Adult; Communication Barriers; Cultural Characteristics; Health Care Surveys; Health Services Accessibility; Hospitals; Pediatric; Hospitals; Teaching; Humans; Language; Middle Aged; Multilingualism; South Africa

Therapists’ views on working with bilingual Spanish-English clients: A qualitative inverstigation - Santiago-Rivera, Azara. L.; Altarriba, Jeanette; Poll, Norma; Gonzalez-Miller, Normaris; Cragun, Cragun (Professional Psychology: Research and Practice, 2009)
Through semistructured interviews, language switching in therapy was examined with 9 bilingual Spanish and English therapists. Therapists were asked about how and when they switched from one language to another during treatment, as well as the ways in which their clients’ switched languages. After the use of consensual qualitative research methods (C. E. Hill et al., 2005; C. E. Hill, B. J. Thompson, & E. N. Williams, 1997), the results revealed that therapists used language switching as a mechanism to establish trust, bond with clients, and promote disclosure through the use of specific phrases or specific words; particularly, the use of Spanish idiomatic expressions (dichos) served to engage, redirect, and increase client self-understanding and awareness. Therapists reported that their clients switched from English to Spanish when recounting experiences that involved certain emotions (e.g., anger) and represented themselves differently depending on the language they were speaking. Therapists also reported that their clients switched from English to Spanish to improve communication and to connect with them. Future directions for research and implications for training and practice are outlined. (PsycInfo Database Record (c) 2025 APA, all rights reserved)

The effects of a language barrier in a South African district hospital - Schlemmer, A.; Mash, B. (South African Medical Journal = Suid-Afrikaanse Tydskrif Vir Geneeskunde, 2006)
BACKGROUND: Communication between health workers and patients at Hottentots Holland Hospital (HHH) is hindered by staff and patients not speaking the same language. HHH is a district hospital in the Cape Town Metropolitan District of the Western Cape where staff mainly speak Afrikaans or English and a large number of patients mainly Xhosa. OBJECTIVES: The study aimed to explore the effects of this language barrier on health workers and patients at HHH. DESIGN: Three focus group interviews were held with 21 members of staff and 5 in-depth patient interviews were conducted. RESULTS: The language barrier was found to interfere with working efficiently, create uncertainty about the accuracy of interpretation, be enhanced by a lack of education or training, cause significant ethical dilemmas, negatively influence the attitudes of patients and staff towards each other, decrease the quality of and satisfaction with care, and cause cross-cultural misunderstandings. CONCLUSION: The effects of the language barrier were considerable and persistent despite an official language policy in the province. The training and employment of professional interpreters as well as teaching of basic Xhosa to staff are recommended.
Keywords: Communication Barriers; Health Services Accessibility; Hospitals; District; Humans; Language; Multilingualism; Outcome Assessment; Health Care; Professional-Patient Relations; South Africa; Surveys and Questionnaires

La santé et les minorités linguistiques : l’approche canadienne au regard de cas internationaux - Traisnel, Christophe; Forgues, Éric (Francophonies d'Amérique, 2009)
Dans notre article, nous présentons une analyse comparative de l’approche canadienne de l’enjeu de la santé pour les communautés francophones en situation minoritaire (CFSM). Nous montrons que l’État canadien a favorisé une démarche de concertation avec les acteurs communautaires. Notre analyse comparative nous a permis de dégager une typologie des politiques linguistiques en matière de santé destinées aux CFSM. Cette typologie permet de situer l’expérience canadienne par rapport à d’autres expériences, parfois proches, mais présentant des perspectives différentes, comme le montrent les cas finlandais, belge et états-unien. La « voie » canadienne paraît originale dans la mesure où elle semble se situer entre un modèle communautaire, à l’instar des pays européens, et un modèle individualisé, à l’instar de ce qui se fait aux États-Unis.